Analysis Of Basic Teachers Professionality In Improving Creativity In The Digital Era - Iskandar, Rossi; MS, Zulela (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
The purpose of this study is to describe the professional competence of teachers in increasing creativity in the digital era. The research method used in this research is qualitative with the type of library research, which is a series of studies relating to the library data collection method, or research where the object of research is explored through a variety of library information with a philosophical and pedagogical approach. The results showed that to drive better change in the world of education with a priority to increase the quality of teachers, it is necessary to have teachers who are creative and have the quality to bring change and innovation both academically and non-academically. Creative teachers always develop diverse learning activities. The learning process in front of the class for creative teachers does not only deliver material but has a sense of responsibility to guide, create, experiment, inspire, and motivate students to continue to be creative.